Cultural and Language Context in Banggai Wedding Ritual: A Hermeneutic Approach - Makka, Misbahul Munir; Kolopita, Abdul Fajri; Tumiwa, Anisa Jihan (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2024)
Wedding rituals occupy a central position in the culture of the Banggai people, Central Sulawesi. The traditional ceremony is full of elements of oral and written traditions that reflect the outlook on life and local wisdom of the Banggai tribe. This paper aims to interpret and understand the traditional wedding ritual of Banggai in the context of its local culture and language through the application of a hermeneutic approach. The research data was sourced from various transcripts and traditional Banggai documents related to the wedding procession, including pantun, syair, prayer, dance, and other traditional practices. These data are then analyzed in depth to uncover the implied meaning behind traditional symbols and texts by always considering the historical background and oral traditions of the Banggai people so that the resulting interpretation is contextual and proportional. The results showed that the traditional Banggai marriage ritual was full of philosophical content and represented the values and views of life upheld by the community. This ritual also acts as a medium for cultural regeneration and transfer of knowledge passed down between generations. With a comprehensive meaning, this study hopes to enrich readers' insights about the nature and essence of the Banggai wedding tradition.